Teachers’ Perceptions of Professional Development in Inquiry-Based Learning Settings - Isa, Naná (My University, 2021)
This dissertation explores the perceptions of teachers in an inquiry-based learning (IBL) setting regarding professional development (PD) in order to empower them in their journey as IBL educators. The research focused on a case study of a primary school in Ireland that follows the International Baccalaureate Primary Years Programme (IB PYP) in line with IBL. This research was conducted during the Covid-19 pandemic, which impacted the research methods as well as the topic being studied. An inquiry cycle was used to frame the research, since it is a tool widely adopted in IBL settings. A qualitative approach was employed to generate data, incorporating document analysis and individual interviews with seven teachers. The transcripts were coded and four main themes emerged: IBL, IBL Teacher Characteristics, IBL PD, and Community of Inquiry. Findings revealed that teachers benefit from formal and informal instances of PD. Findings also suggested that embracing collaboration and providing teachers with the time to meet in a safe space are key in developing a community of inquiry. Modelling and reflection have been highlighted as key components of effective PD. Finally, this research found that teachers are more willing to participate in and benefit from PD if they can assess their own needs and be active participants in finding PD opportunities. Time has emerged as the main barrier to PD, followed by funding. Insights from this research may prove useful to schools and organizations that value and promote IBL as well as PD policymakers.
Keywords: Inquiry-based learning; Inquiry cycle; inquiry-based International Baccalaureate; Teacher empowerment; Professional Development; Inquiry-based learning